Academic Antagonism and the 'Resetting' of the Northern Ireland 'Problem', 1969–1970: Owen Dudley Edwards vs. Hugh Trevor-Roper. Issue 2 (2nd April 2016) - Lambkin, Brian
Abstract: An important intervention has been made in the discourse about the Northern Ireland conflict, demonstrating how the 'setting' and 'resetting' of the conflict as a 'problem' by academics is itself problematic, and calling for more work on the vexed relationship between the production of scholarly work and its impact on the conflict [Zalewski, M. & Barry, J. (Eds). (2006) Special issue, intervening in Northern Ireland: critically rethinking representations of the conflict, Critical Review of International Social and Political Philosophy, 9(4), pp. 477–634; Zalewski, M. & Barry, J. (Eds) (2007) Intervening in Northern Ireland: Critically Rethinking Representations of the Conflict (London: Routledge)]. This article responds to that call by examining 'academic antagonism' – the tendency of academics to engage in competitive or combative discourse to the detriment of collaborative or accommodating discourse – in relation to the first academic 'setting' of the Northern Ireland 'problem' by Barritt and Carter [(1962) The Northern Ireland Problem: A Study in Group Relations (Oxford: Oxford University Press)]. Close study is made of two of the first 'resettings' by Trevor-Roper [(1969b) Why Ulster Fights: Professor Hugh Trevor-Roper analyzes the historical background to the conflict in Ireland, Réalités, December, 48–53] and Dudley Edwards [(1970) The Sins of our Fathers: roots of conflict in Northern Ireland (Dublin: Gill and Macmillan)], and the 'violent' effects of their antagonism are exposed. This offers new insight into the origins of the ensuing intractable 'meta-conflict' or 'conflict about the conflict' [McGarry, J. & O'Leary, B. (1995) Explaining Northern Ireland: Broken Images (Oxford: Blackwells)]. It is suggested that a large-scale study of academic antagonism (and accommodation) in relation to successive 'resettings' of the Northern Ireland 'problem' is needed to rebuild trust in the academy with regard to its role in 'dealing with the past'.